Use of Immunoglobulin Variable-Region Genes by Normal Subjects and Patients with Systemic Lupus Erythematosus - Hansen, A.; Dörner, T.; Lipsky, P.E. (International archives of allergy and immunology, 2000)
Antibodies to specific autoantigens are serological hallmarks of systemic autoimmune diseases. These autoantibodies are thought to represent a consequence of immune dysregulation in these conditions, and, in part, have been shown to be involved in their pathologic consequences. However, the mechanisms that lead to the production of autoantibodies are still unknown. The observation that certain autoantibodies are frequently encoded by a limited number of immunoglobulin (Ig) variable-region gene segments suggested that a bias in the development of the Ig repertoire might play a role in the tendency to develop autoimmunity. Whether the use of these individual gene segments is random or different in normal subjects and patients with systemic autoimmune disorders remains a matter of controversy. New approaches for the analysis of variable-region genes from unstimulated individual human B cells employing the single-cell polymerase chain reaction have provided new insights in the B cell repertoire of both normal subjects and patients with systemic autoimmune diseases. Using this approach, the analysis of nonproductive and productive Ig variable-region gene rearrangements made it possible to distinguish molecular processes, as manifested in the nonproductive repertoire, from subsequent selection influences. An initial study in a patient with systemic lupus erythematosus has led to the hypothesis that the molecular generation of the B cell repertoire is similar in patients and normal subjects but subsequent influences and, most notably, extensive mutations and receptor editing differ significantly in shaping the peripheral IgV gene use by persons with autoimmune diseases.